Potential Implications of Verbal Sexual Violence Through Humor: A Forensic Linguistic Analysis - Dhion Meitreya Vidhiasi (Journal of linguistics, culture and communication, 2025)
Verbal expressions of non-physical sexual violence are frequently perceived merely as “jokes.” This study investigates the possibility of a verbal sexual violence offense perpetrated by a religious leader during a question-and-answer session with a participant at a spiritual event. The data consists of a video uploaded to an Instagram account during the question-and-answer session. News articles from liputan6.com, rctiplus.com, and merdeka.com are used prevent research bias and to support the data transcription and interpretation. The dialogue among Person 1, Person 2, and Person 3 in the video was subsequently transcribed to analyze the speech acts employed. This research uses a qualitative descriptive methodology. This study qualifies and explains speech acts through Weigand’s (2010) taxonomy of dialogic speech acts. This study’s results indicate that Person 1 employs representative and directive speech. This dominance indicates that Person 1 attempted to persuade all attendees at the event that the “joke” regarding Person 3 was factual. Furthermore, this dominance indicates that Person 1 has been found to have violated Law No. 12 of 2022 through the commission of a criminal act of verbal sexual violence. The taxonomy of dialogic speech acts has effectively facilitated the analysis of potential criminal acts of verbal sexual violence.